Bagaimana konflik pekerjaan-keluarga dapat membahayakan kinerja? Integrasi Conservation of Resources Theory - Ikhsan Maksum; Nur Laili Fikriah; Agus Iqbal Hawabi (Jurnal Ekonomi Modernisasi, 2022)
The development of research related to work-family conflict is overgrowing. However, there are still various gaps involving the mediating role to investigate the indirect effect of work-family conflict on performance. This study aims to examine the mediating role of psychological well-being in the pathway of the effect of work-family conflict on performance. The researcher involved 81 respondents, most of whom were college employees. The basic theory in this study uses the conservation of resources theory. The study results found that psychological well-being could fully mediate the indirect effect of work-family conflict on employee performance. Based on the Conservation of Resources Theory, that workers who already have families are more likely to engage with conflicts between work and family. Logically, workers who cannot manage resources, they will channel resources only on one goal, namely at their work. Thus, their family environment lacks attention and ultimately the conflict between work and family will occur in a worker who cannot manage their resources.